The Feminist and the Bible: Hermeneutical Alternatives - Osiek, Carolyn (Hervormde teologiese studies, 1997)
Amid the varieties of feminist interpretive methods in biblical scholarship, this article suggests a general typology of approaches: rejection of the claims of biblical authority; acceptance of those claims with critique of oppressive interpretations; revisionism, which holds to the possibility of reconstructing the lost experience of women in the texts; reliance on symbol and image of the feminine to convey meaning; and finally, the liberation critique of oppressive structures. An appreciation and critique is offered for each alternative.